Adolescent girls' infant and young child nutrition knowledge levels and sources differ among rural and urban samples in Bangladesh - Hoddinott, John F.; Karachiwalla, Naureen; Ledlie, Natasha; Roy, Shalini (Wiley, 2016)
In many low‐income countries, girls marry early and have children very soon after marriage. Although conveying infant and young child nutrition (IYCN) knowledge to adolescent girls in time is important to ensure the well‐being of their children, little is known about the best ways to convey these messages. This study examines the extent of, and sources from which adolescent girls derive IYCN knowledge in order to inform the design of programmes that convey such information. Data on adolescent girls aged 12–18 was collected in 2013 in 140 clusters of villages in rural areas (n = 436), and 70 clusters of slums in urban areas (n = 345) in Bangladesh. Data were analysed using multivariable Poisson regression models. In both the urban and rural samples, girls' schooling is positively and significantly associated with IYCN knowledge (P < 0.01 and P < 0.10, respectively). IYCN knowledge of adolescent girls' mothers is also associated with adolescents' IYCN knowledge in both urban and rural samples, but the magnitude of association in the urban sample is only half that of the rural sample (P < 0.01 and P < 0.10, respectively). In Bangladesh, efforts to improve knowledge regarding IYCN are typically focused on mothers of young children. Only some of this knowledge is passed onto adolescent girls living in the same household. As other messaging efforts directed towards mothers have only small, or no association with adolescent girls' knowledge of IYCN, improving adolescent girls' IYCN knowledge may require information and messaging specifically directed towards them. © 2016 John Wiley & Sons Ltd